CRYOBALLOON ABLATION FOR ATRIAL FIBRILLATION IN DIFFERENT ANATOMY OF PULMONARY VEINS - T. Yu. Chichkova; S. E. Mamchur; A. N. Kokov; N. S. Bokhan; E. A. Khomenko; I. N. Mamchur (Российский кардиологический журнал)
Aim. To evaluate the results of cryo-ablation in a variety of pulmonary veins (PV) anatomy.Material and methods. Into prospective randomized study, 94 patients were included, with tolerant to drug treatment atrial fibrillation (AF), age 55,9±9,8 y.o., of those 48 males and 46 females. The median of an arrhythmic anamnesis lasted for 4 (1,5; 5) years. Seven patients had undergone radiofrequency ablation (RFA) of cavotricuspid isthmus (CTI), 5 had recurrent AF after former RFA. Seven — at the moment of admittance, had persistent AF. Under the framework of preoperational investigation, all patients underwent contrast multispiral computed tomography of the heart. The architectonics of the PV was assessed: number, diameter, specifics of opening, thrombi. Depending on the anatomy of the PV, patients were selected to 2 groups — typical and variant anatomy. The prevalence of a variety of PV anatomy was 13,8%. By the key clinical characteristics, the groups were comparable. All patients underwent cryoballoon isolation of the PV with the ArcticFront28 mm and ArcticFront Advance28 mm catheters. All patients with variants of PV anatomy underwent the procedure with the 2nd generation catheter. For verification of the PV isolation, Achieve catheter was used. In all cases of PV isolation it was verified as the enter and exit block, with no adenosine test.Results. In the group of variation PV anatomy, in 11 cases, there was collector of the left PV or their opening into the left atrium (LA) by common ostium. There were no significant differences in a direct specifics of procedures: duration of ablation (75 (46,2; 105) vs 60 (52; 70) min, p=0,40) and duration of fluoroscopy (17 (16; 23,7) vs 20 (16,3; 23,8) min, p=0,64). The analysis of non-related groups showed significantly higher prevalence of complications development in the variation anatomy group, and the prevalence of nervus phrenicus palsy (NPP) (6,9 vs 3,7%) as vascular approach complications (3,19 vs 2,5%), were comparable (p>0,05). Also, in patients with the common ostium of PV there was pericarditis development more frequently during post-operation period, that led to anti-inflammatory treatment prescription. Long-term analysis shows the significant decrease of the method efficacy in variation PV anatomy, especially in presence of collector/vestibule of PV, even with the 2nd generation balloon usage.Conclusion. Existence of a collector/vestibule of the left PV is associated with significant worsening of the long-term results of cryoballoon ablation, even in 2nd generation devices utilization.